Echocardiographic Hemodynamic Heterogeneity of Advanced Heart Failure Patients as Compared to Patients with "Pre-Heart Failure" - Elena-Laura ANTOHI; Oliviana GEAVLETE; Razvan RADU; Ovidiu CHIONCEL; Serban MIHAILEANU (Sciendo, 2021)
Background: Advanced heart failure (HF) represents a clinical entity encompassing severely symptomatic HF with severely dysfunctional left ventricles (LV). The single most important parameter for defining severe LV dysfunction and indicating the prescription of evidence-based therapies is LV ejection fraction (EF). We sought to investigate the hemodynamics by echocardiography in a cohort of advanced HF patients during a hospitalization for HF decompensation and assess the relevant differences when compared to a control cohort of asymptomatic patients with minor structural/functional cardiac abnormalities. Methods and results: In this prospective study we selected 18 advanced HF patients and 12 asymptomatic preHF patients with only minor structural/functional abnormalities. The 2 groups were clearly delineated by size parameters (end -systolic and -diastolic diameters and volumes respectively, with very low p values p<0.0001). Hemodynamic parameters were significantly different as well in the advanced HF group vs the 'pre-HF' group, including: ventricular-arterial coupling 1.745 vs. 0.895, p=0.0007; cardiac power output 0.762 vs. 0.932, p=0.044, systolic times ratio 0.406 vs. 0.200, p=0.0001. There were no significant differences for neither effective arterial elastance (Ea) and nor for cardiac index. Inside the advanced HF group, no correlation between LVEF and other parameters were found and none of these parameters could predict outcome. We observed a highly skewed variation of Ea in advanced HF patients. Conclusion: Among the most severe HF patients, the hemodynamic interaction between the dysfunctional LV and the compensatory response of the peripheral system is heterogenous and cannot predict outcome by single parameters. In these patients, assessment of cardiac performance should no longer rely on LEVF alone.